Features of pregravid preparation in women with connective tissue dysplasia - I Yu Ilina; Yu E Dobrokhotova; V O Malikova; A A Chikisheva (IP Berlin A.V., 2018)
The prevalence of multifactorial pathology among the population is manifested by a high frequency of extragenital pathology during pregnancy, contributing to the emergence of various combined pathological processes. Women with connective tissue dysplasia are at high risk for reproductive disorders with respect to a number of complications during pregnancy (threatened miscarriage, preeclampsia, placental insufficiency). In the period of pregravid preparation, in addition to well-known prescriptions, Selzinc® of pronounced antioxidant properties can be recommended for use, this complex has a beneficial effect on the course of pregnancy due to the replenishment of trace elements, the deficiency of which can lead to the development of various complications.